(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Dexmedetomidine is alpha agonist drug with multiple uses in perioperative anaesthesia care. The drug deceases the requirement of inhalational agents. This study is a randomized, double-blinded trial that aimed to investigate the use of the sedative and analgesic medication dexmedetomidine in patients undergoing elective major abdominal surgeries under general anaesthesia. Methods: Sixty patients scheduled to undergo General anesthesia were included in the study and were randomly assigned to either the Dexmedetomidine group or the Placebo group. The study was approved by the hospital's ethical committee and had specific inclusion and exclusion criteria for patients. The interventions included pre-medication and standard monitoring, as well as the administration of a range of drugs, including dexmedetomidine and a placebo, during the induction and maintenance of anaesthesia. The study aimed to maintain a specific level of sedation and monitor various vital signs throughout the surgery. The BIS index was maintained and the sevoflurane requirements were analysed. Results: The total sevoflurane volume required by the Dexmedetomidine was less when compared to placebo group. Sevoflurane volume consumed by Dexmedetomidine group was 30% less in the 1st hour, 23% less in the 2nd hour and 22% less in the 3rd hour when compared to the placebo group. The study found that the mean duration of surgery in the Dexmedetomidine group (162.97±19.32) was not significantly different from that in the Placebo group (159.50±18.88) with a P value of 0.442. However, the hourly average sevoflurane consumption was significantly less in the Dexmedetomidine group (8.34±1.94 ml) compared to the Placebo group (13.55±2.36 ml) at the end of the first hour of surgery, and the difference remained statistically significant at the end of the 2nd and 3rd hour of surgery. Conclusion: Intraoperative use of Dexmedetomidine infusion has decreased the amount of sevoflurane required when compared to placebo group under BIS guided anaesthesia without any major adverse events like bradycardia and hypotension. It also provided additional postoperative analgesia as indicated by the VAS score.